2020
DOI: 10.52417/ojms.v1i2.152
|View full text |Cite
|
Sign up to set email alerts
|

Information and Communication Technology in Managing Small and Medium Enterprises in Nigeria

Abstract: Information Communication Technology has generally been acclaimed as an important tool exploited by medium and large-scale enterprises for boosting profitability and enhancing viability. Though Small and Medium Scale Enterprises (SMEs) constitutes a major percentage of businesses in most countries, their ICT adoption rate is still low. This study examined the role of ICT as a tool that SMEs can deploy for the economic development of Nigeria. A questionnaire was employed and administered to a total of 175 SMEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was determined that the firm's high-income contribution might be ascribed to the fact that they worked 10 hours per day, 28 days per month, and eleven months out of the year [14] . A study revealed poor Information and Communication Technology (ICT) adaptation, knowledge management, and metoo orientation, which makes MSMEs unprofitable [15] when other studies acknowledged the multiple issues that influence MSMEs [16] .…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that the firm's high-income contribution might be ascribed to the fact that they worked 10 hours per day, 28 days per month, and eleven months out of the year [14] . A study revealed poor Information and Communication Technology (ICT) adaptation, knowledge management, and metoo orientation, which makes MSMEs unprofitable [15] when other studies acknowledged the multiple issues that influence MSMEs [16] .…”
Section: Introductionmentioning
confidence: 99%
“…Despite these contributions, cursory observations show that nearly four of every five SMEs do not survive beyond five years of inception because of inexperience, weak ambidexterity, and poor knowledge sharing. Abubakar and Hussaina [7] recognized the numerous challenges affecting MSMEs, and Igboeli and Bisallah [8] indicated a low level of Information and Communication Technology (ICT) adaptation, knowledge management, and me-too orientation, making them unprofitable.…”
Section: Introductionmentioning
confidence: 99%